STRUCTURE AND STYLE OF TRADITIONAL ENGLISH BALLADS - Eldorbek Erkin og’li Khamitov; Turdimuratova Mexribanu Janabaevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Traditional English ballads constitute a significant and long-standing genre of folk literature that embodies the social values, historical experiences, and cultural traditions of early English society. This research examines the structural patterns and stylistic characteristics that define traditional English ballads, focusing on their narrative organization, poetic framework, and expressive techniques. In terms of structure, these ballads are typically composed of four-line stanzas, frequently following alternating iambic tetrameter and iambic trimeter, along with consistent rhyme schemes such as ABAB or ABCB, which enhance rhythmic flow and support oral performance. Stylistically, traditional English ballads are notable for their clarity and conciseness, prioritizing narrative progression over detailed description. The frequent use of dialogue allows the storyline to unfold dynamically, engaging the audience while intensifying emotional impact. Repetition and refrains serve both mnemonic and artistic purposes, reinforcing key moments and aiding memorization in oral transmission. Additionally, ballads often employ formulaic expressions, symbolic elements, and narrative restraint, encouraging listeners to actively interpret the events rather than relying on explicit explanation. The oral and anonymous nature of traditional English ballads has played a crucial role in shaping their stable yet flexible form. Although variations developed as the ballads were transmitted across generations, their fundamental structural and stylistic features remained intact. This study demonstrates that the balance between formal simplicity and narrative effectiveness enabled traditional English ballads to serve as both a form of popular entertainment and a vehicle for preserving collective cultural identity. Consequently, the enduring appeal of traditional English ballads lies in their well-defined structure and distinctive style, which continue to influence literary traditions.